Dexamethasone inhibits regeneration and causes ventricular aneurysm in the neonatal porcine heart after myocardial infarction. (July 2020) - Tao, Zhonghao; Loo, Szejie; Su, Liping; Abdurrachim, Desiree; Lalic, Janise; Lee, Teck Hock; Chen, Xin; Tan, Ru-San; Zhang, Jianyi; Ye, Lei
Abstract: Aims: Recently, we demonstrated that the hearts of neonatal pigs (2-day old) have regenerative capacity, likely driven by cardiac myocyte division, but this potential is lost immediately after postnatal day 3. However, it is unknown if corticosteroid, a broad anti-inflammatory agent, will abrogate the regenerative capacity in the hearts of neonatal pigs. The aim of the current study is to evaluate the effect Dexamethasone (Dex), a broad anti-inflammatory agent, on heart regeneration, structure, and function of the neonatal pigs' post-myocardial infarction (MI). Methods and results: Dex (0.2 mg/kg/day) was injected intramuscularly into the neonatal pig (age: 2 days postnatal) during the first week post-MI. Myocardial scar and left ventricular function were determined by cardiac magnetic resonance (CMR) imaging. Bromodeoxyuridine (BrdU) pulse-chase labeling, histology, immunohistochemistry, and flow cytometry were performed to determine inflammatory cell infiltration, CM cytokinesis, and myocardial fibrosis. Dex injection during the first-week suppressed acute inflammation post-MI in the pig hearts. It inhibited BrdU incorporation to pig CMs and CM cytokinesis via inhibiting aurora-B protein expression which was associated with mature scar formation and thinned walls at the infarct site. CMR imaging showed Dex caused left ventricular aneurysm and poor ejection fraction. Conclusions: Dex inhibited CM cytokinesis and functional recovery and caused ventricular aneurysm in the hearts of 2-day old pigs post-MI. Graphical abstract: Unlabelled Image Highlights: Dexamethasone inhibits heart regeneration in the hearts of 2-day old pigs after acute myocardial infarction (AMI). Dexamethasone causes ventricular aneurysm in the hearts of 2-day old pigs after AMI. Dexamethasone inhibits cardiac macrophage expansion in the hearts of 2-day old pigs after AMI. Dexamethasone inhibits myocyte cytokinesis in the hearts of 2-day old pigs after AMI.